Analysis of Particulate Matter Emissions and Performance of the Compression Ignition Engine Using Biodiesel Blended Fuel - Bhangwar, S.; Ghoto, S. M.; Abbasi, A.; Abbasi, M. K.; Rind, A. A.; Luhur, M. R.; Khan, Z.; Rajput, U. A.; Mastoi, S. (Engineering, Technology & Applied Science Research, 2022)
As the world becomes more urbanized, the market for petroleum products increases. The supply of crude oil-based products such as diesel, gasoline, and natural gas is limited. Furthermore, natural resources are finite and their reservoirs are located in certain parts of the globe. Countries with low to no fossil fuel resources are experiencing a scarcity of petroleum products, necessitating the exploration of alternative energy resources. In this research, tests regarding the exhaust particulate emission, sound pressure level, and performance have been carried out using samples from diesel and biodiesel (waste cooking oil) blended fuel. Two fuel samples have been used, B25 (biodiesel 25% and 75% diesel) and 100% diesel as a baseline in a CI engine at constant RPM of 1350 and variable loads of 0.0 to 1.6 at an interval of 0.2Kg-m. The results show that particulate emissions are reduced by about 7.29% when using biodiesel blended fuel, whereas brake-specific fuel consumption of biodiesel blended fuel has decreased as brake power increased, and brake thermal efficiency increased as brake power increased. The sound pressure level was measured from different locations of the engine (back, front, left) and for varying load. The results show that B25 produces less noise than D100 in each case.